2013
DOI: 10.1155/2013/236371
|View full text |Cite
|
Sign up to set email alerts
|

The Mean Platelet Volume in Patients with Retinal Vein Occlusion

Abstract: Background. The aim of this study was to investigate the mean platelet volume (MPV) of patients with retinal vein occlusion (RVO). Methods. Hundred and ninty-three patients with the diagnosis of RVO and 83 healthy control subjects were included in this retrospective study. Retinal vein occlusion was diagnosed based on clinical examination. All patients and control subjects underwent complete ocular examination. MPV, hematocrit, hemoglobin, and platelet count of the participants were recorded. The data of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 23 publications
0
35
0
5
Order By: Relevance
“…MPV has been studied in a few ocular vascular disorders. Our team reported an increase in MPV in patients with retinal vein occlusion (RVO) and ocular Behçet's disease (30,31) . Ateş et al found a significant increase in MPV in patients with diabetic retinopathy (32) .…”
Section: Discussionmentioning
confidence: 99%
“…MPV has been studied in a few ocular vascular disorders. Our team reported an increase in MPV in patients with retinal vein occlusion (RVO) and ocular Behçet's disease (30,31) . Ateş et al found a significant increase in MPV in patients with diabetic retinopathy (32) .…”
Section: Discussionmentioning
confidence: 99%
“…Also it has been studied that MPV is elevated in occlusion diseases and hence MPV can be used as predictive tool for identifying risk for retinal vein occlusion patients. Higher level of mean platelet volume is risk factor for patients with occlusions is been presented [13]. Macular edema is cause of vision disturbance.…”
Section: International Journal Of Computer Applications (0975 -8887)mentioning
confidence: 97%
“…Platelets play an important role in the pathogenesis of various thrombo-occlusive diseases, such as anterior ischemic optic neuropathy [6], ischemic and hemorrhagic stroke [7], and RVO [8]. Mean platelet volume (MPV) is a major indicator of the production rate and size of platelets, and has been associated with the activities of platelets [9, 10].…”
Section: Introductionmentioning
confidence: 99%